The Effect of Leverage and Sales Growth on Tax Avoidance - Sulistyawati, Ismah; Willy, Siska (Review of Accounting and Business, 2025)
Introduction/Main Objectives: This study aims to see how the influence of leverage and sales growth on tax avoidance. Background Problems: The study was conducted on property and real estate sector companies listed on the Indonesia Stock Exchange for the period 2021-2023. The research population was 74 property and real estate sector companies listed on the Indonesia Stock Exchange for the period 2021-2023. Novelty: The effect of leverage and sales growth to tax avoidance in property and real estate companies listed on the Indonesia Stock Exchange (IDX) in 2021–2023. Research Methods: The sample was processed using purposive sampling method to filter certain criteria, so that a sample of 17 companies was obtained for 3 periods and resulted in 51 observation data. The type of data used is secondary data obtained through financial reports on the official website of the Indonesia Stock Exchange (www.idx.co.id). Data analysis was tested using multiple linear regression tests with the help of SPSS Version 25 software. Finding/Results: The results of this study indicate that partially leverage and sales growth affect to tax avoidance. Then, simultaneously the leverage and sales growth variables affect to tax avoidance. Conclusion: The managerial implication of this finding is that company management needs to pay attention to funding structures and sales growth strategies in order to manage tax liabilities optimally without violating applicable regulations.